2015
DOI: 10.3892/mco.2015.644
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of epidermal growth factor receptor mutation in non-small-cell lung cancers in the Gulf region

Abstract: Abstract. The aim of the present study was to determine the prevalence of epidermal growth factor receptor mutations (EGFRmut) in the Gulf region (GR) and its correlation with demographic and clinical characteristics. A multisite retrospective study was conducted, including institutions from Saudi Arabia, the United Arab Emirates and Qatar. All consecutive patients with non-small-cell lung cancer tested for EGFRmut were eligible. Data collected included demographic information, disease characteristics and EGFR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
20
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 12 publications
7
20
1
Order By: Relevance
“…Age, sex, and histological subtypes of included patients were reported in all of the studies; however, data on smoking status were only available in 9 studies whereas data on ethnical background were precised in an exclusive study reported in the Gulf region [ 16 ]. These characteristics were summarized using means and standard deviations for the ordinal variables and frequencies for the categorical ones.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Age, sex, and histological subtypes of included patients were reported in all of the studies; however, data on smoking status were only available in 9 studies whereas data on ethnical background were precised in an exclusive study reported in the Gulf region [ 16 ]. These characteristics were summarized using means and standard deviations for the ordinal variables and frequencies for the categorical ones.…”
Section: Resultsmentioning
confidence: 99%
“…(%) Ever-smokers, No. (%) Overall 383 (41.1%) 550 (58.9%) Lebanon Naderi et al [ 9 ] 44 (21.9%) 157 (78.1%) Fakhruddin et al [ 10 ] 59 (76.6%) 18 (23.4%) Kattan et al [ 11 ] 39 (22.9%) 131 (77.1%) Egypt Zaki et al [ 12 ] No data No data Turkey Unal et al [ 13 ] 5 (10.4%) 43 (89.6%) Bircan et al [ 14 ] 6 (26.1%) 17 (73.9%) Saudi Arabia (SA) Al-Kuraya et al [ 15 ] 38 (80.9%) 9 (19.1%) SA-UAE-Qatar Jazieh et al [ 16 ] 134 (58.3%) 96 (41.7%) SA-UAE-Egypt Jazieh et al [ 17 ] No data No data Morocco Errihani et al [ 18 ] 58 (42.3%) 79 (57.7%) …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…reported that in a retrospective study which conducted in the gulf region, EGFR mutations were detected overall in 28.7% with a prevalence of 32.46% in adenocarcinoma which is higher than reported in western patients but still lower than the Asian population. [ 122 ]…”
Section: Initial Treatment Of Epidermal Growth Factor Receptor Mutatimentioning
confidence: 99%